Medication Review in Turkish Older Adults at Community Pharmacy: A Pilot Study by Using Medication Appropriateness Index - ALTIPARMAK, ÖZNUR; SANCAR, MESUT; OKUYAN, BETÜL (My University, 2022)
Objective: The study aimed to evaluate medication review in older adults (≥65 years) at a community pharmacy by identifying the prevalence of potentiality inappropriate medication and calculating medication appropriateness index. Methods: This descriptive study was carried out in a community pharmacy for six months. The older adults (≥65 years) using one or more medications were included. During clinical pharmacist-led medication review; the medication appropriateness index was calculated for each medication of older adults. Potentially inappropriate medications were evaluated according to the 2019 American Geriatrics Society Beers Criteria®. Result: Among a hundred older adults, 46.0% were female. The median age of the patients was 75.5 (IQR, 68.0-78.8). The median number of medications was 9.0 (7.0-10.0). Polypharmacy has been detected in 97.0% of the patients. At least one potentially inappropriate medication was detected in 63.0% of them. The median score of medication appropriateness index score was 53.0 (IQR: 38.6-67.9). Conclusion: To best our knowledge, this is the first study of clinical pharmacist-led medication review by calculating the medication appropriateness index carried out at a community pharmacy in Turkey. There was a high rate of potentially inappropriate medication with a higher score of medication appropriateness in older adults. This study highlights the importance of medication review led by the clinical pharmacist at community pharmacy to optimize medication usage in older adults. Keywords: Older adults, clinical pharmacist, medication appropriateness index, potentially inappropriate medication
Keywords: Tıp; Dahili Tıp Bilimleri; Tıbbi Ekoloji ve Hidroklimatoloji; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Medical Ecology and Hydroclimatology; Health Sciences; TIP, ARAŞTIRMA VE DENEYSEL; Klinik Tıp; Klinik Tıp (MED); MEDICINE, RESEARCH & EXPERIMENTAL; CLINICAL MEDICINE; Clinical Medicine (MED); Araştırma ve Teori; İncelemeler ve Referanslar (tıbbi); Research and Theory; Reviews and References (medical); Older adults; clinical pharmacist; medication appropriateness index; potentially inappropriate medication; POTENTIALLY INAPPROPRIATE MEDICATIONS; STOPP CRITERIA; BEERS CRITERIA; SCREENING TOOL; POLYPHARMACY; CARE; PREVALENCE; PEOPLE; Older adults; clinical pharmacist; medication appropriateness index; potentially inappropriate medication